Pyoderma gangrenosum: a challenge for the plastic surgeon - Francisco Felipe Góis de Oliveira; Mariana Fernandes; Ana Maria Nogueira Giacoia; Osvaldo Saldanha; Marcos Ricardo Menegazzo; Eugênio Gonzalez Cação; Osvaldo Saldanha (Revista Brasileira de Cirurgia Plástica)
Introduction: Pyoderma gangrenosum (PG) is a chronic and rare autoimmune dermatosis. Its etiology remains poorly understood, being idiopathic in 25 to 50% of cases; in others, it is associated with systemic diseases with autoimmune background and has an incidence of 2 to 3 cases per 1 million per year. In Brazil, the rate is 0.38 cases per 10,000 clinical visits, and women between the second and fifth decades of life are the most affected. The clinical presentation is variable, and the ulcerous form, which appears on a previous scar, is the most prevalent. Case Report: A 39-year-old, previously healthy female underwent reduction mammoplasty, and later developed a necrotic ulcer on a vertical left breast scar. Debridement of devitalized tissue was performed, with significant worsening despite antibiotic therapy. The appearance suggested PG. Treatment with oral and topical corticosteroids was then initiated with remission. Conclusions: PG represents a diagnostic challenge, and can be confused with surgical site infection.